2020
DOI: 10.1186/s13017-020-0290-x
|View full text |Cite
|
Sign up to set email alerts
|

Associated abdominal injuries do not influence quality of care in pelvic fractures—a multicenter cohort study from the German Pelvic Registry

Abstract: Background: Pelvic fractures are rare but serious injuries. The influence of a concomitant abdominal trauma on the time point of surgery and the quality of care regarding quality of reduction or the clinical course in pelvic injuries has not been investigated yet. Methods: We retrospectively analyzed the prospective consecutive cohort from the multicenter German Pelvic Registry of the German Trauma Society in the years 2003-2017. Demographic, clinical, and operative parameters were recorded and compared for tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 37 publications
(35 reference statements)
0
8
0
Order By: Relevance
“…Therefore, it is of significant forensic relevance to evaluate pelvic structures in detail. Pelvic fractures in particular are associated with fatal bleeding and are associated with collateral abdominal and urogenital injuries [5][6][7]. If present, pelvic fractures can double the mortality of multiple injured patients [3].…”
mentioning
confidence: 99%
“…Therefore, it is of significant forensic relevance to evaluate pelvic structures in detail. Pelvic fractures in particular are associated with fatal bleeding and are associated with collateral abdominal and urogenital injuries [5][6][7]. If present, pelvic fractures can double the mortality of multiple injured patients [3].…”
mentioning
confidence: 99%
“…However, a postponement over three weeks has been proven to be associated with a worse surgical outcome, especially regarding reduction quality in pelvic and acetabulum fractures. 43,45 Further, Glass et al reported a significant decrease in clinically relevant surgical site infections, following definitive early fracture fixation, including long bones, pelvic ring, acetabular fractures, and spinal fusions, even in the presence of an open abdomen when compared with delayed fracture fixation. 44 Similarly, Vallier et al reported that early definitive fracture fixation including spine fixations are safe in polytrauma patients as part of the "Early Appropriate Care" protocol 26 .…”
Section: Abdominal Injury and Extremity Injury Managementmentioning
confidence: 99%
“…Unstable pelvic fracture is the manifestation of pelvic ring destruction under direct or indirect violence which may be life-threatening [12]. It requires a careful and interdisciplinary decision-making regarding the therapeutic regime [2]. The principle of early diagnosis and treatment is to maintain hemodynamic stability.…”
Section: Discussionmentioning
confidence: 99%
“…Unstable pelvic ring fracture is severe injuries, related with high-energy trauma [1]. Main causes are tra c accidents or falls from different heights [2]. High mortality and complication rates are associated with hemodynamic instability and mechanical malfunction of pelvic ring [3].…”
Section: Introductionmentioning
confidence: 99%